INTEGRATED APPROACH IN TEACHING FOREIGN LANGUAGES IN TECHNICAL HIGHER EDUCATIONAL INSTITUTIONS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
The article under discussion reveals integrated approach in teaching foreign languages in technical higher educational institutions. The author of the article considers that the use of integrated approach in teaching process leads to increased motivation for learning general subjects and a foreign language itself, and to the formation of readiness for professional activity in the context of integration processes in the economic, social and political spheres of life.